Vibration responses of a two-span three-support rotor system with sliding bearing elevation change - Z. Zhou; G. Bin; C. Li; Y. Gao; M. Bayjid Md (Mechanical Sciences)
The two-span three-support rotor is a typical structure in rotating machinery such as steam turbines and water pumps. The alteration in bearing elevation can result in oil film instability, rotor rub impact, and other malfunctions. In extreme cases, this can cause excessive wear of couplings and other components, leading to accidents. This study derives the dynamic equation of a two-span three-support rotor that accounts for variations in bearing elevation. Meanwhile, the influence of different sliding bearing elevations on the misalignment excitation of the coupling and the stiffness damping coefficient of the bearing is considered, and the vibration response of each bearing is also investigated. Corresponding experiments are designed and conducted to validate the findings. The findings indicate that after raising the elevation of bearing 3 from 1.5 to 2 mm, the amplitude of the fundamental frequency (1×) at bearing 2 is reduced by 438 %, whereas the amplitude at the second harmonic (2×) is increased by 128 %. This increase in misalignment excitation causes the axis orbit of disk 1 to change from a crescent shape to a petal shape. This study offers theoretical insights and empirical data that may assist in the structural design and fault diagnosis of two-span three-support rotors.